Розвиток індивідуального стилю діяльності менеджера в процесі професійної підготовки - Воробйова, Євгенія Вячеславівна (НТУ "ХПІ", 2012)
The article analyzes the main features of the individual style of professional activity, defined the components of the individual manager's style,as well as researched and identified the development of individual style of the manager in training.
Keywords: індивідуальний стиль діяльності; менеджер; професійна діяльність менеджера; професійна підготовка менеджерів